Communicative language teaching method at improving students’ macro and micro-skills of reading comprehension in intensive reading course - Tri Jampi Setiyorini; Yuyun Yulia; Hasti Robiasih (Universitas Islam Sultan Agung, 2022)
Several university students seem to meet difficulties in reading comprehension. The lecturer needs to use a suitable method for teaching reading; one of them is Communicative Language Teaching (CLT). This research aims to analyse whether CLT improves students' macro-skills and micro-skills of reading comprehension in an intensive reading course. Research method employed in this study is a case study. The research participants were 21 first-semester students of a private university in Indonesia. The instruments were close-ended questionnaires and open-ended interviews. The findings showed that there was a significant improvement on students' macro-skills and micro-skills of reading comprehension in an intensive reading course after implementing CLT. Students also contend that learning reading using CLT is fun, engaging, and understandable. The researchers conclude that the CLT contributes learners’ macro-skills and micro-skills of reading comprehension in the intensive reading course.